2022
DOI: 10.3390/app12115442
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble-Learning-Based Prediction of Steel Bridge Deck Defect Condition

Abstract: This study developed an ensemble-learning-based bridge deck defect condition prediction model to help bridge managers make more rational and informed steel bridge deck maintenance decisions. Using the latest data from the NBI database for 2021, this study first used ADASYN to solve imbalance problems in the data, then built six ensemble learning models (RandomForest, ExtraTree, AdaBoost, GBDT, XGBoost, and LightGBM) and used a grid search method to determine the hyperparameters of the models. The optimal model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Ensemble learning can be widely used in defect analysis and remaining useful life prediction in engineering. Li and Song 133 build six models based ensemble learning to predict bridge deck defect, and the learning model based on XGBoost is found optimal, whose explanatory agrees with the fact. Li et al 134 propose an ensemble learningbased prognostic approach that considers the influence of time-dependent degradation to assess the remaining useful life.…”
Section: Ensemble Learningsupporting
confidence: 54%
“…Ensemble learning can be widely used in defect analysis and remaining useful life prediction in engineering. Li and Song 133 build six models based ensemble learning to predict bridge deck defect, and the learning model based on XGBoost is found optimal, whose explanatory agrees with the fact. Li et al 134 propose an ensemble learningbased prognostic approach that considers the influence of time-dependent degradation to assess the remaining useful life.…”
Section: Ensemble Learningsupporting
confidence: 54%
“…The study employs the Adaptive Synthetic (ADASYN) sampling technique to handle imbalanced data, enhancing the prediction quality. Li et al [35] aimed to assist bridge managers in making informed maintenance decisions for steel bridge deck defects by developing an ensemble-learning-based prediction model. The research employed ADASYN to address data imbalance issues in the 2021 NBI database and built six ensemble learning models with optimized hyperparameters through grid search.…”
Section: Adasyn Data Balancingmentioning
confidence: 99%
“…Yet, machine learning algorithms frequently encounter challenges such as outliers and imbalanced datasets, which can reduce accuracy. Research has demonstrated that addressing these issues by applying the Isolation Forest (iForest) method to remove outliers [23][24][25][26][27] and utilizing Adaptive Synthetic Sampling (ADASYN) for balancing imbalanced data [28][29][30][31][32][33][34][35] can lead to improved predictive system performance.…”
Section: Introductionmentioning
confidence: 99%
“…Datadriven artificial intelligence techniques can break through artificial empirical perception and eliminate dependence on humans [12,13]. Integrated learning methods represented by XGBoost models have become increasingly popular among researchers in engineering prediction problems in recent years [14,15]. Lyngdoh et al used several popular machine learning models for concrete strength prediction.…”
Section: Introductionmentioning
confidence: 99%